Life cycle assessment of a lignin nanoparticle biorefinery: Decision support for its process development. (1st February 2020) - Koch, Daniel; Paul, Marco; Beisl, Stefan; Friedl, Anton; Mihalyi, Bettina
Abstract: The production of lignin nanoparticle from wheat straw within an innovative biorefinery is currently under development and a life cycle assessment (LCA) was applied to investigate the environmental implications of a prototypical biorefinery model. The model is based upon gathering the life cycle inventory through available experimental information, process simulation results and commercial datasets. The goal of the LCA is decision support for the further development of this early-stage technology from an environmental impact perspective. The appropriate scope is set to a cradle-to-gate investigation regarding lignin nanoparticle production. Relevant impact categories were chosen for a holistic assessment: eutrophication potential (EP), global warming potential (GWP), human toxicity potential (HTP), water use and consumption and the water scarcity index. Scenarios were designed with process variations to obtain their influence on the environmental impacts. The focus of these variations is on the precipitation and purification process steps. Within the scenario analysis results, GWP and HTP show a similar behavior in identifying the thermal energy demand and virgin ethanol as the hotspots, as well as agreeing on the best-case scenario: 2 times precipitation volume, 90% permeate removal per membrane and two membrane separation units. Within the water assessment, only the water use indicator shows the same best-case scenario. The EP results identify the ethanol leakage within the liquid residues from the solvent recovery as the crucial hotspot in this assessment and therefore favors a different scenario. The LCA provided a deeper understanding of the environmental impacts from the innovative production of lignin nanoparticles, it suggests using lower precipitation volume and ethanol recovery only up to a certain point. These outcomes can be utilized as decision support for further sustainable process developments. Graphical abstract: Image 1 Highlights: The eutrophication potential results show a unique behavior in the scenario assessment compared to the other categories. Not all impact categories prefer the same scenario: the best case depends on the impact category. A lower volume for the solvent and pH shifting precipitation is preferred in any case. A tradeoff exists between the required virgin ethanol and the required process utilities for the ethanol recovery.